2020
DOI: 10.3897/pls2020571/06
|View full text |Cite
|
Sign up to set email alerts
|

Cyperus-dominated vegetation in the eastern Po river

Abstract: The ephemeral vegetation dominated by Cyperus sp. pl. was surveyed and analyzed along the eastern trait of the Po River (Po Plain, Italy). Two formerly described communities were recognized: Cyperetum esculenti and Amaranthus tuberculatus-phytocoenon. A third greater cluster is assigned to a new association: Cyperetum micheliano-glomerati. It is characterized by Cyperus glomeratus, C. michelianus, C. odoratus and C. squarrosus, that have been detected on over 75 % of the relevés. The main floristic and ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Po River hydrological basin comparatively extends at higher latitude and altitude and is plausibly characterized by a higher C3/C4 biomass ratio, with respect to the Reno River ratio. Moreover, it has to be noted that, the embankments of Po River are dominated by Cyperus vegetation (Pellizzari, 2020), which are C3-plants whose  13 C signature is extremely negative (Puttock et al, 2012;Laceby et al, 2014;Meier et al, 2014). In addition,  13 C negativization in suspended particles of Po river water can also be induced by comparatively higher development of fresh water plankton (Søballe and Kimmel, 1987;Finlay and Kendall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Po River hydrological basin comparatively extends at higher latitude and altitude and is plausibly characterized by a higher C3/C4 biomass ratio, with respect to the Reno River ratio. Moreover, it has to be noted that, the embankments of Po River are dominated by Cyperus vegetation (Pellizzari, 2020), which are C3-plants whose  13 C signature is extremely negative (Puttock et al, 2012;Laceby et al, 2014;Meier et al, 2014). In addition,  13 C negativization in suspended particles of Po river water can also be induced by comparatively higher development of fresh water plankton (Søballe and Kimmel, 1987;Finlay and Kendall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore; Dobignard & Chatelain (2010-2020 in their synonymous and bibliographic index of the North African flora cite this species as a neophyte for Azores and Canary Islands, confirmed by Verloove (2014). We also referred to the website of the herbarium of the botanist researcher Gérard De Bélair (http://gdebelair.com/tax/ famicype.html), who did not note the presence of C. eragrostis in Algeria.…”
Section: Introductionmentioning
confidence: 88%
“…For several decades C. eragrostis has been naturalized in various European and Asian countries, some of which have a warm and relatively moist Mediterranean climate. Thus, we cannot exclude that global warming has enabled alien species to expand into regions in which they previously could not survive and reproduce (Walther et al, 2009;Pellizzari, 2020). In this context, Hoffmann (1994) reported that the occurrence of C. eragrostis in Germany as a consequence of global climate change.…”
Section: Conclusion and Implication For Weed Managementmentioning
confidence: 97%